Exploratory Graph Analysis of the Strengths and Difficulties Questionnaire for Aboriginal and/or Torres Strait Islander Children - Santiago, Pedro Henrique Ribeiro; Manzini Macedo, Davi; Haag, Dandara; Roberts, Rachel; Smithers, Lisa; Hedges, Joanne; Jamieson, Lisa (Frontiers in Psychology, 2021)
In Australia, one of the most frequently used measures for assessing Aboriginal and/or Torres Strait Islander children’s social and emotional wellbeing is the Strengths and Difficulties Questionnaire (SDQ). Previous state-level validations studies indicated problems with the original five-factor SDQ structure, especially with the Peer Problems dimension. The aim of the current was to use a novel psychometric methodology, namely Exploratory Graph Analysis (EGA), to evaluate the caregiver-informed SDQ version 4-10 years dimensionality at a national level in Australia. Data were used from two independent longitudinal studies, the Longitudinal Study of Indigenous Children and South Australian Aboriginal Birth Cohort. The caregiver-informed SDQ version 4-10 years was applied across several study waves, including more than 4,000 responses. To conduct EGA, Gaussian Graphical Models were estimated with Least Absolute Shrinkage and Selection Operator. 2,500 bootstrap samples were also employed to investigate dimension and item stability. The findings indicated robust evidence against the construct validity of the original five-factor SDQ structure. Future studies should conduct direct external validation of the findings with Aboriginal and/or Torres Strait Islander parents/carers and community groups to develop guidelines for future use of the instrument among Aboriginal and/or Torres Strait Islander children in Australia.